1995
DOI: 10.1021/bi00046a025
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Purification of the Light Chain of Botulinum Neurotoxin A: A Single Mutation Abolishes Its Cleavage of SNAP-25 and Neurotoxicity after Reconstitution with the Heavy Chain

Abstract: Botulinum neurotoxin type A (BoNT/A) selectively and irreversibly inhibits acetylcholine release from peripheral nerve endings. While the toxin's heavy (H) chain contributes to neuronal binding and internalization, its light (L) chain is a Zn(2+)-dependent endoprotease that intracellularly cleaves synaptosomal-associated protein of M(r) = 25 kDa (SNAP-25). For research and clinical exploitation of this uniquely-acting neurotoxin, recombinant wild-type L chain was produced together with a mutant in which His227… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 25 publications
3
27
0
2
Order By: Relevance
“…It was not possible to estimate an EC 50 for recLH N /A(H227Y) and recLH N /A(H227Y)-ECL due to insufficient cleavage of SNAP-25; however, data indicated that the endopeptidase activity of the recLH N /A(H227Y) species was reduced ϳ300-fold compared with recLH N /A. This is in reasonable agreement with the data previously reported for this H227Y mutation in the light chain of BoNT/A (32).…”
Section: Purification and Characterization Of Lhsupporting
confidence: 85%
“…It was not possible to estimate an EC 50 for recLH N /A(H227Y) and recLH N /A(H227Y)-ECL due to insufficient cleavage of SNAP-25; however, data indicated that the endopeptidase activity of the recLH N /A(H227Y) species was reduced ϳ300-fold compared with recLH N /A. This is in reasonable agreement with the data previously reported for this H227Y mutation in the light chain of BoNT/A (32).…”
Section: Purification and Characterization Of Lhsupporting
confidence: 85%
“…The zinc coordinating residues identify a primary sphere of residues essential to the catalytic function. Site-directed mutagenesis of TeNT and BoNT/A residues of the zinc-binding motif (11)(12)(13) and of the conserved glutamic acid 271 of TeNT (14,15) confirmed the essential role of these residues in catalysis. From the analysis of the available structures, it appears that a secondary layer of residues is present at the active site of BoNT/A and BoNT/B.…”
mentioning
confidence: 73%
“…The largest body of work on the expression and purification of recombinant fragments containing the enzyme activity has been carried out on the A serotype, and a wide range of LC/A fragments have been purified from the soluble fraction and using refolding techniques [33][34][35][36][37][38][39][40][41][42][43]. From these various reports, it is apparent that the resulting LC/A proteins differ considerably in stability and retained protease activity.…”
Section: Recombinant Expression Of Fragments Containing the Protease mentioning
confidence: 99%